Protocol to detect m22G modification on single tRNA iso-decoders by immuno-northern blotting - Sseu-Pei Hwang; Katherine Barondeau; Catherine Denicourt (STAR Protocols, 2025)
Summary: tRNA modifications are highly dynamic and play crucial roles in regulating gene expression. Here, we present an assay for analyzing N2, N2-dimethylguanosine (m22G) modifications on tRNAs using an antibody-based detection approach. We describe steps for isolating tRNAs from human cells via ion-exchange chromatography, capturing specific tRNA iso-decoders on streptavidin magnetic beads, and detecting modifications through immuno-northern blotting. This approach enables researchers to investigate other tRNA modifications using specific antibodies or downstream approaches such as mass spectrometry.For complete details on the use and execution of this protocol, please refer to Hwang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.